Forest Stewardship Council and Responsible Wood certification in the integrated pest management in Australian forest plantations - Lemes, Pedro G.; Zanuncio, José C.; Jacovine, Laércio A.G.; Wilcken, Carlos F. [UNESP]; Lawson, Simon A. (Elsevier, 2021)
Certification programs may include market access benefits for those business that have certified voluntarily, but there are also other consequences, such as the ban on the use of certain chemical pesticides imposed by the Forest Stewardship Council (FSC) that can negatively affect integrated pest management. The Programme for the Endorsement of Forest Certification (PEFC) was created in response to FSC standards and includes national certification schemes such as the Responsible Wood (RW), previously known as the Australian Forestry Standard (AFS). The objective of this study was to evaluate the impacts of FSC and RW/PEFC certification on practices of integrated pest management from the perspective of Australian forest growers. Questionnaires were emailed to all organizations in Australia with forest plantations certified by FSC and/or RW/PEFC. The questionnaire addressed the importance of forest pest groups, pest control techniques, chemical pesticides (insecticides and herbicides) in derogation; the advantages and disadvantages of integrated pest management related to the certification; and satisfaction with certification in relation to pest management. The two insecticides in derogation were considered unnecessary by most of Australian growers. FSC promoted more changes in integrated pest management than RW. Half the FSC-certified companies stated that they had greater costs associated with integrated pest management to adequately meet certification. RW-certified growers were more satisfied than FSC-certified ones, but both groups stated that they would maintain certification in a scenario without further insecticide derogation. The main changes in pest management for FSC-certified companies were with preventive techniques that reduce the use and dependence on insecticides. The environmental and social side of FSC prevailed in these changes. Raising certification rigor can increase costs, making certification impracticable, forcing companies to adopt less restrictive schemes or simply not certify.
Keywords: Australian forestry standard; Forest entomology; PEFC; Pesticides; Stakeholders; Sustainable forestry